The Regulatory Framework Governing Traditional Arbitration in Resolving Islamic Banking Disputes in Malaysia: The Time for Change - Mohamad Fateh Labanieh; Mohammad Azam Hussain; Nazli Mahdzir (Jurnal Hukum Novelty, 2021)
Introduction to The Problem: Malaysia has established its place as a global leader in Islamic banking due to the considerable efforts made by the Malaysian lawmakers to enhance the Islamic banking dispute resolution framework and provide the Islamic banking disputants with several resolution mechanisms, such as traditional arbitration. However, using traditional arbitration in resolving Islamic banking disputes is not free from criticisms. Therefore, there is a need to find an alternative or enhanced form of traditional arbitration mechanism.Purpose/Objective Study: This article examines the regulatory framework governing traditional arbitration in resolving Islamic banking disputes in Malaysia.Design/Methodology/Approach: This article is based on doctrinal legal research Methodology. Primary data was secured from several sources, such as Acts, Laws, and Court Cases. While secondary data was collected from books, journal articles, and online databases. Both data are analyzed by using critical and analytical approaches.Findings: It is found that Arbitration Act 2005 (Act 646) and I-Arbitration Rules 2018 have been subjected to several amendments to align with the international norms and best practices. However, Malaysian lawmakers should start thinking out of the box by reinforcing the Islamic banking disputants with an effective resolution mechanism known as electronic arbitration (hereinafter referred to as “e-arbitration”). Doing so would facilitate prompt access to justice in Islamic banking disputes in Malaysia.Paper Type: Research Article